REMOVAL OF Cd2+ IN WASTEWATER USING ZEOLITIC IMIDAZOLATE FRAMEWORK-8 (ZIF-8) AS SYNTHESIS ADSORBENT - Rahmatul Fajri; Fira Asfahani; Yulida Amri; Jofrishal Jofrishal (UIN AR-RANIRY, 2023)
Zeolitic Imidazole Framework-8 (ZIF-8) has been synthesized by dissolving Zn(NO3)2.4H2O and 2-MeIM into a methanol solvent and solvothermal method. The synthesized ZIF-8 will be applied as a cadmium (Cd) adsorbent in Polluted water. Several characterization methods were conducted, including XRD, FTIR, and AAS. The XRD analysis shows that the prominent characteristic peaks of ZIF-8 at an angle of 2θ = 7,25o; 10,26o; 12,57o; 16,22o; and 17,86o. At the same time, the FTIR analysis showed the presence of functional groups of Zn-N, C-N, C=N, C=C, and C-H on aromatic 2-Methyl Immidazole as an indication that ZIF-8 has been completely established. Based on the result, the AAS method performed to analyze ZIF-8 ability to adsorb Cd in the water showed that Cd ions adsorption increased at pH 6 and 8 while decreasing at pH 7.